The effect of complex exercises by a variety of means in developing the skill of shooting and controlling the ball with the head of young football players (Journal of the College of Basic Education, 2022)
The importance of the research lies in conducting this study by designing exercises with a variety of questions prepared by the study that contributed to the development of the skill of shooting and bouncing the ball with the head for junior footballers, because the exercises are of great importance in developing the performance of the head ball (shooting and controlling the technical ball with the head), watching who was able to search for a sample With the players, the research sample consisted of a sample of the junior football players of the Olympic Champion project, who are (50) players, aged (50) 14 - 15 years, and according to the requirements, design, design and design that were distributed to the players Two experimental and control groups (15) experimental groups for each group, and one of the two groups was selected, the experimental group, the other the control group, and the remaining players. The results of the research were presented, analyzed and discussed, and included the results of sports and motor skill. With the head kick, the most important recommendations were the adoption and generalization of the compound exercises prepared by the researcher within the players training curricula because they lead to the development of the level of players at ages, and the coaches of the Olympic Champion project - specialized schools in football must be acquainted with the importance of compound exercises and how to apply them by scientific methods.